HDI trimer based fluorine containing urethane methacrylates for hydrophobic photocured coatings - ÇAKMAKÇI, EMRAH (TAYLOR & FRANCIS INC, 2019)
In this work, hexamethylene diisocyanate (HDI) trimer based two urethane methacrylates were synthesized by reacting 2-hydroxyethyl methacrylate (HEMA) and a fluoroalcohol with HDI trimer. Due to the high viscosity of the fluorinated methacrylates, they were applied onto glass substrates after mixing with tripropylene glycol diacrylate (TPGDA). The performance of the fluorinated resins were compared to a fluorine free HDI trimer based trimethacrylate. The TPGDA diluted formulations were better in terms of surface wettability than the neat resins. TPGDA diluted fluorinated resins exhibited a water contact angle of 109 degrees +/- 2. All coatings exhibited high surface hardness (4H and 5H) and good adhesion. [GRAPHICS] .
Keywords: Fluorine; HDI; photocure; hydrophobic; low surface energy; SURFACE-PROPERTIES; ACRYLATE; ENERGY; SPACER; POLYACRYLATES; CHAIN; FILMS